1985
DOI: 10.1038/clpt.1985.36
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemodynamic effects of pinacidil and hydralazine in essential hypertension

Abstract: In a double-blind, randomized, crossover study, the effects of intravenous pinacidil, 0.2 mg/kg, were compared with those of hydralazine, 0.3 mg/kg, before and after beta-adrenoceptor blockade in six subjects with hypertension. Both drugs equally reduced total peripheral resistance by about 40%. Pinacidil reduced mean blood pressure by an average of 30 mm Hg, while the reduction after hydralazine was 10 mm Hg. The difference in antihypertensive effect resulted from greater increases in heart rate, cardiac cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…These hemodynamic effects remained constant for 1 hour. Similar immediate hemodynamic effects have previously been reported from a group of six hypertensive patients studied by Carlsen et al [28] and from a similar group by Goldberg [29].…”
Section: Potassium Channel Openersupporting
confidence: 70%
See 1 more Smart Citation
“…These hemodynamic effects remained constant for 1 hour. Similar immediate hemodynamic effects have previously been reported from a group of six hypertensive patients studied by Carlsen et al [28] and from a similar group by Goldberg [29].…”
Section: Potassium Channel Openersupporting
confidence: 70%
“…An increase SI also contributes to the rise in CI. Since this may be abolished by beta blockade, the rise in SI is most likely to be secondary to sympathetic stimulation [28].…”
Section: Potassium Channel Openermentioning
confidence: 99%
“…These observations were made in single dose and short term studies (Carlsen et al , 1983(Carlsen et al , 1985Kardel et Drug Invest. 3 (5) 1991.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it has been suggested that the mechanism of action is dependent upon the opening of potassium channels in vascular smooth muscle cells (Southerton et al 1988;Videbaek et al 1988). Previous investigations have shown a close correlation between the serum concentration of pinacidil and the effect on blood pressure (Carlsen et al , 1983(Carlsen et al , 1985Kardel et al 1981). The biological halflife (t.;,) in serum is short, approximately 2 to 3 hours (Carlsen et al 1983).…”
mentioning
confidence: 83%
“…However, as with any potent vasodilator, its clinical use is sometimes associated with some characteristic and undesirable side effects which can lead to treatment withdrawal (Ward, 1984;Zachariah et al, 1986;McBurney et al, 1988b;Goldberg et al, 1988Goldberg et al, , 1989a. In order to limit these side effects, the relationships between P plasma concentrations and P antihypertensive effects were investigated at an early stage (Carlsen et al, 1981(Carlsen et al, , 1983(Carlsen et al, , 1985Kardel et al, 1981;Ward et al, 1984), and a range of effective and safe P plasma concentrations was determined. Simultaneously, controlled release formulations were developed in an attempt to avoid too high peak concentrations (Carlsen et al, 1983;Laher and Hickey, 1985;McBurney et al, 1985McBurney et al, , 1987McBurney et al, , 1988a.…”
Section: Introductionmentioning
confidence: 99%